2019
DOI: 10.3389/fonc.2019.00314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compound Kushen Injection, a Natural Compound Mixture, and Its Identified Chemical Components on Migration and Invasion of Colon, Brain, and Breast Cancer Cell Lines

Abstract: Traditional Chinese Medicines are promising sources of new agents for controlling cancer metastasis. Compound Kushen Injection (CKI), prepared from medicinal plants Sophora flavescens and Heterosmilax chinensis , disrupts cell cycle and induces apoptosis in breast cancer; however, effects on migration and invasion remained unknown. CKI, fractionated mixtures, and isolated components were tested in migration assays with colon (HT-29, SW-480, DLD-1), brain (U87-MG, U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 49 publications
5
27
0
Order By: Relevance
“…Based on our previous publications, perturbed regulation of genes in these pathways and annotated by these terms was associated with the observed cell viability and apoptotic effects CKI on cancer cells (10, 14). Other terms showing perturbation of metabolic processes and cell migration identified in this study, such as “pyrimidine metabolism,” “steroid biosynthesis,” and “positive regulation of locomotion,” also showed up in our previous research on the effects of CKI (25). Altogether, these results indicated that Kushen was very important to the major molecular consequences of CKI treatment, and perturbed most of the biological functions perturbed by CKI, resulting in reduced viability and and increased apoptosis in cancer cells.…”
Section: Resultssupporting
confidence: 72%
“…Based on our previous publications, perturbed regulation of genes in these pathways and annotated by these terms was associated with the observed cell viability and apoptotic effects CKI on cancer cells (10, 14). Other terms showing perturbation of metabolic processes and cell migration identified in this study, such as “pyrimidine metabolism,” “steroid biosynthesis,” and “positive regulation of locomotion,” also showed up in our previous research on the effects of CKI (25). Altogether, these results indicated that Kushen was very important to the major molecular consequences of CKI treatment, and perturbed most of the biological functions perturbed by CKI, resulting in reduced viability and and increased apoptosis in cancer cells.…”
Section: Resultssupporting
confidence: 72%
“…These pathways regulate cell proliferation and apoptosis (P53, RTK-RAS-MAPK, PI3K-Akt-mTOR and NRF2) and metastasis/invasion (TGF-beta). Moreover, CKI also targets angiogenesis and tumor microenvironment regulating pathways through VEGFA/VEGFR2 and cytokine signaling (B cell receptor, T cell receptor and FC-epsilon signaling) respectively ( Supplementary Table 5 ), which is consistent with a previous finding 52 . Other reports have shown that CKI directly regulates cell migration 53 ; and apoptosis in breast cancer 52 .…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, CKI also targets angiogenesis and tumor microenvironment regulating pathways through VEGFA/VEGFR2 and cytokine signaling (B cell receptor, T cell receptor and FC-epsilon signaling) respectively ( Supplementary Table 5 ), which is consistent with a previous finding 52 . Other reports have shown that CKI directly regulates cell migration 53 ; and apoptosis in breast cancer 52 . Cell cycle, proliferation and apoptosis, metastasis/invasion, and angiogenesis were the main targeted carcinogenesis processes in this cell line ( Table 3 ).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have demonstrated that CKI can alter the cell-cycle, induce apoptosis and reduce proliferation and migration in various cancer cell lines 6,1618 . CKI also killed leukaemia cells via the Prdxs/ROS/Trx1 signalling pathway in an acute myeloid leukaemia patient-derived xenograft model and caused cell-cycle arrest in U937 leukaemia-derived cells 19 .…”
Section: Discussionmentioning
confidence: 99%